Effects of calcein on the levels of antioxidant enzymes and lipid peroxidation in juvenile silver carp, Hypophthalmichthys molitrix. (11th December 2020) - Lü, Hongjian; Chen, Linghan; Xie, Zhenhui; Fu, Mei; Su, Shengqi; Yao, Weizhi
Abstract: Standard single‐exposure of calcein (CAL) was conducted on juvenile silver carp, Hypophthalmichthys molitrix, to examine its effects on antioxidant enzyme levels and lipid peroxidation. Juveniles were exposed to different concentrations of CAL solutions (0, 100, 300, 500 and 700 mg/L) for different immersion periods (12, 24, 48, 72 and 96 hr). Increased glutamate‐oxaloacetate transaminase, glutamate‐pyruvate transaminase and alkaline phosphatases activities were assumed to be due to CAL‐induced hepatic damage, probably because of the high potential of CAL to accumulate in fish hepatopancreas. Higher CAL concentrations (>300 mg/L) and prolonged immersion periods (>48 hr) could lead to greater toxicity in juvenile silver carp and, to a certain degree, damage the gills and hepatopancreas. The antioxidant responses in the gills and hepatopancreas result in successful elimination of the excess CAL‐induced reactive oxygen species for CAL exposure ≤24 hr. Our results confirmed that the toxic effects of CAL on antioxidant enzyme levels and lipid peroxidation in juvenile silver carp depended on both CAL concentrations and duration of exposure. Moreover, concentration of CAL solutions and the immersion period should be, respectively, restricted to ≤300 mg/L and ≤24 hr, when CAL is used for immersion marking juvenile silver carp.